Effect of Cadmium Application Alone or Along with FYM on Spinach Grown on Calcareous and Non-calcareous Soil - Chandrawal, Ashwani Kumar; Kumar, Amrendra (International Journal of Bio-resource and Stress Management, 2023)
Heavy metals such as Cd, Ni, Cr, Cu, Pb and Hg are common environmental pollutants, particularly in areas with anthropogenic pressure. Their presence in the atmosphere, soil and water, even in traces can cause serious problems to all organisms. The mobilization of heavy metals into the biosphere by human activity has become an important aspect in the geochemical cycling of these metals. Hence experiments were conducted to study the cadmium toxicity in calcareous and non-calcareous in spinach crop. Two types of soil were collected in bulk, one from calcareous belt and another from non-calcareous belt with two levels of FYM application i.e. 0 t ha-1 and 10 t ha-1. Varying levels ranging from 0 to 120 ppm of Cd were applied with or without FYM in both the soils and replicated thrice in a completely randomized design. Spinach was grown for 45 days for various observations. The biomass yield started to decrease at 5 and 10 ppm levels of Cd. Application of FYM increased the Cd content as well as uptake in crop and soils. The toxic levels of Cd in spinach were 0.58 µg g-1 for calcareous soil and 3.73 µg g-1 for non-calcareous soil. The toxic level of cadmium in calcareous soil for spinach were 2.3 µg g-1, while in non-calcareous soil it was 3.00 µg g-1.